2017
DOI: 10.1051/e3sconf/20171700011
|View full text |Cite
|
Sign up to set email alerts
|

The studies on waste biodegradation by Tenebrio molitor

Abstract: Abstract.As cities are growing in size with a rise in the population, the amount of plastic waste generated is increasing and becoming unmanageable. The treatment and disposal of plastic waste is an urgent need of our present and future. It has been proved recently that mealworms, the larvae of Tenebrio molitor Linnaeus, are able eat styrofoam, a common polystyrene product. Polystyrene is one of the most widely used plastics, the scale of its production being several million tons per year. Tenebrio molitor is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 7 publications
0
8
0
4
Order By: Relevance
“…Marshall School students (Duluth MN, USA) reported 33 mg PS 100 worms −1 d −1 , within the range of previous tests; a team at the University of Queensland, St. Lucia, Australia, reported that local mealworms consumed PS at a rate of 13 mg PS 100 worms −1 d −1 ; a team in Bandar Lampung, Indonesia, reported that PS foam feeds supported mealworm growth, and the feed had no significant effect on larvaemortality (Nukmal et al, 2018); and students reported formation of beetles from larvae when fed PS plus bran, confirming prior reports (Yang et al, 2015a. Mealworms were also observed consuming PE, an observation now documented in the peer-reviewed literature , as well as other plastics, including PVC and PLA, as reported by an academic team in Poland (Boźek et al, 2017). Fig.…”
Section: Effect Of Antibiotics On Ps Degradationmentioning
confidence: 58%
See 1 more Smart Citation
“…Marshall School students (Duluth MN, USA) reported 33 mg PS 100 worms −1 d −1 , within the range of previous tests; a team at the University of Queensland, St. Lucia, Australia, reported that local mealworms consumed PS at a rate of 13 mg PS 100 worms −1 d −1 ; a team in Bandar Lampung, Indonesia, reported that PS foam feeds supported mealworm growth, and the feed had no significant effect on larvaemortality (Nukmal et al, 2018); and students reported formation of beetles from larvae when fed PS plus bran, confirming prior reports (Yang et al, 2015a. Mealworms were also observed consuming PE, an observation now documented in the peer-reviewed literature , as well as other plastics, including PVC and PLA, as reported by an academic team in Poland (Boźek et al, 2017). Fig.…”
Section: Effect Of Antibiotics On Ps Degradationmentioning
confidence: 58%
“…Other academic researchers have reported mealworm consumption of PVC and PLA (Boźek et al, 2017). Chewing of plastic into small fragments increases the surface area of the ingested plastic and thus likely enhances enzymatic depolymerization, but depolymerization of the ingested plastic was not completed in the 14-18 h transit time through the mealworm gut.…”
Section: Significance Of the Ubiquity Of Ps Degradation By Mealwormsmentioning
confidence: 96%
“…The results of PS shown a higher degree of utilization compared to the studies of [16], where the reduction was only 9.0%, and [20,41], where the reduction was 31.0% and 39.1%, respectively. Mealworms from three Chinese regions of Guangzhou, Tai'an, Shenzhen utilized 57.5%, 34.4%, and 52.4% of PS, respectively [19].…”
Section: Rate Of Ps Pu1 Pu2 and Pe Consumption By Mealwormsmentioning
confidence: 60%
“…For this reason, it was not possible to compare the results with other authors [16,17,[31][32][33][34], who have currently focused mainly on the biodegradation of plastics in various insect species. The studies [35] on waste biodegradation by Tenebrio molitor) described the weight loss of groups of larvae in individual types of plastics after 21 days from −15% to −19%. There were also losses in this work.…”
Section: Influence Of Feed On Life Cyclementioning
confidence: 99%